Do scientific objects have a life (which may end)?. Issue 2 (June 2021) - Arabatzis, Theodore
Argument: The aim of this article is to make a case for the pertinence of a biographical approach to the history of scientific objects. I first lay out the rationale of that approach by revisiting and extending my earlier work on the topic. I consider the characteristics of scientific objects that motivate the biographical metaphor, and I indicate its virtues and limitations by bringing out the positive and negative analogies between biographies of scientific objects and ordinary biographies. I then point out various ways in which scientific objects may pass away and argue that their demise should be conceptualized as a process. Finally, I sketch the history of the concept of "ether" in nineteenth and early twentieth century physics and suggest that it lends itself particularly well to a biographical treatment. To that effect, I discuss the identity, heuristic character, and recalcitrance of the ether and examine the reasons that may have led to its passing.